Targeting PTEN-defined breast cancers with a one-two punch. Issue 1 (December 2015) - Maggi, Leonard; Weber, Jason
Abstract With tremendous advances in sequencing and analysis in recent years, a wealth of genetic information has become available to identify and classify breast cancer into five main subtypes - luminal A, luminal B, claudin-low, human epidermal growth factor receptor 2-enriched, and basal-like. Current treatment decisions are often based on these classifications, and while more beneficial than any single treatment for all breast cancers, targeted therapeutics have exhibited limited success with most of the subtypes. Luminal B breast cancers are associated with early relapse following endocrine therapy and often exhibit a poor prognosis that is similar to that of the aggressive basal-like breast cancers. Identifying genetic components that contribute to the luminal B endocrine resistant phenotype has become imperative. To this end, numerous groups have identified activation of the phosphatidylinositol 3-kinase (PI3K) pathway as a common recurring event in luminal B cancers with poor outcome. Examining the pathways downstream of PI3K, Fu and colleagues have recreated a human model of the luminal B subtype of breast cancer. The authors were able to reduce expression of phosphatase and tensin homolog (PTEN), the negative regulator of PI3K, using inducible short hairpin RNAs. By varying the expression of PTEN, the authors effectively conferred endocrine resistance and recapitulated the luminal B gene expression signature. Using this systemin vitro andin vivo, they then tested the ability of selective kinase inhibitors downstream of PI3K to enhance current endocrine therapies. A combination of fulvestrant, which blocks ligand-dependent and -independent estrogen receptor signaling, with protein kinase B inhibition was found to overcome endocrine resistance. These findings squarely place PTEN expression levels at the nexus of luminal B breast cancers and indicates that patients with PTEN-low estrogen receptor-positive tumors might benefit from combined endocrine and PI3K pathway therapies.